2008
DOI: 10.1111/j.1600-0838.2007.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training improves the role of high‐density lipoprotein antioxidant and reduces plasma lipid peroxidation in type 2 diabetes mellitus

Abstract: In this study, we analyzed the effect of aerobic exercise training (AET) and of a single bout of exercise on plasma oxidative stress and on antioxidant defenses in type 2 diabetes mellitus (DM) and in healthy control subjects (C). DM and C did not differ regarding triglycerides, high-density lipoprotein cholesterol (HDL-c), insulin, and HOMA index at baseline and after AET. To measure the lag time for low-density lipoprotein (LDL) oxidation (LAG) and the maximal rate of conjugated diene formation (MCD), partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 52 publications
4
36
1
8
Order By: Relevance
“…Furthermore, intense aerobic exercise training corresponds to 60% to 85% maximum heart rate (2,3,5), resulting in increased PON1 activity, while no significant changes occur in LDL, HDL, and TG levels. In contrast, other researchers have reported that vigorous and moderate aerobic exercise trainings have no significant effects on PON1 activity and lipid profile levels (9)(10)(11). Also, no significant change in PON1 activity and lipid profile has been reported following resistance exercise trainings (2).…”
Section: Introductionmentioning
confidence: 51%
“…Furthermore, intense aerobic exercise training corresponds to 60% to 85% maximum heart rate (2,3,5), resulting in increased PON1 activity, while no significant changes occur in LDL, HDL, and TG levels. In contrast, other researchers have reported that vigorous and moderate aerobic exercise trainings have no significant effects on PON1 activity and lipid profile levels (9)(10)(11). Also, no significant change in PON1 activity and lipid profile has been reported following resistance exercise trainings (2).…”
Section: Introductionmentioning
confidence: 51%
“…Therefore, the relationships found in the present study may reflect developments in PON1 activities. Some studies showed that there were changes in PON1 activity or antioxidant capacity of HDLs in the absence of changes in BLLP levels and antioxidant capacity 56,57) . These study results support our proposition that exercise can change PON1 release and its activity by internal developments in organisms without any quantitative changes in other factors, such as physical composition, performance, and BLLP levels in welltrained athletes Post-T.…”
Section: Training Effects On Blood Tdpon1 Activities and Pon1p Involvmentioning
confidence: 99%
“…c P found by the repeated measures ANOVA test (inter group). (29). Although aerobic exercise did not alter the amount of HDL in the aerobic group, the lack of exercise in the control group showed significantly decreased HDL.…”
Section: Discussionmentioning
confidence: 99%